Properties of Foamed Concrete according to Replacement Ratio of Blast Furnace Slag - Cho, Eun Seok; Lime, Jeong Jun; Lee, Sang Soo (International Journal of Advanced Science and Technology, 2019)
Abstract Background/Objectives: Conventional lightweight foamed concrete uses cement during the manufacturing process, which inevitably releases carbon dioxide during the raw material production process, which is a problem of carbon emission. This study was conducted to evaluate the utilization of blast furnace slag as an alternative to cement as an industrial by - product. Methods/Statistical analysis: In order to evaluate the use of blast furnace slag as an alternative to cement as an industrial by-product, this study replaced the blast furnace slag with 0, 20, 40, 60 (%) compared with cement and examined its characteristics. Findings: As the replacement rate of blast furnace slag increased, the density decreased and the fluidity tended to increase. Absorption and thermal conductivity are highly affected by density. As the substitution rate of blast furnace slag increased, the density decreased, and as a result, the water absorption tended to increase and the thermal conductivity tended to decrease. The overall compressive strength of the slag decreased with increasing blast furnace slag replacement rate at 7 days of age. In case of blast furnace slag replacement rate of 20 and 40 (%), the strength value was higher than that of OPC alone. Experiments have shown that blast furnace slag is replaced with a part of cement used for lightweight foamed concrete and shows similar properties. Keywords: Blast Furnace Slag, CO2, Foamed Concrete, Greenhous gases, Recycling